THE USE OF CRITICAL LITERACY APPROACH TO INTENSIFY THE STUDENTS’ CRITICAL READING ABILITY AT THE SMPN 2 SUNGGUMINASA - Nur Afni; Ummi Khaerati Syam; Farisha Andi Baso (English Language Teaching Methodology, 2021)
The objective of the research aims to find whether the use of critical literacy approach is effective in improving the students’ critical reading ability at the Smpn 2 Sungguminasa. The researcher used a Pre-experimental method with one group pre-test and post-test, and data collection based on the test. The sample of this research was VIII.6 class which consists of 34 students. The sample was taken by using purposive sampling technique. Based on the findings of the research, the research findings indicate that improvement of the students’ critical reading through the use of a critical literacy approach at the eighth-grade students of Smpn 2 Sungguminasa was improved. It was proved by the mean score of the pre-test (64.14%) and the mean score of the post-test (83.44%); it showed that the students’ critical reading in the post-test was higher than pre-test. Besides, the test value (13.980) which was higher than T-table value (1.692).